2016
DOI: 10.1007/s00296-016-3438-y
|View full text |Cite
|
Sign up to set email alerts
|

Computed tomography of pulmonary changes in rheumatoid arthritis: carcinoembryonic antigen (CEA) as a marker of airway disease

Abstract: Rheumatoid arthritis (RA) classically affects the joints, but can present extra-articular manifestations, including pulmonary disease. The present study aimed to identify possible risk factors or laboratory markers for lung involvement in RA, particularly the presence of rheumatoid factor (RF), anti-citrullinated peptide antibodies (ACPA), and tumor markers, by correlating them with changes observed on chest high-resolution computerized tomography (HRCT). This cross-sectional study involved RA patients who wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 36 publications
2
6
0
Order By: Relevance
“…Studies have reported that high CEA levels in serum and bronchoalveolar lavage uid might connected with mucous embolism in asthma patients 17,18 . Milene Caroline Koch al have also shown that increase CEA levels associated with airway changes in rheumatoid arthritis patients such as bronchial wall thickening, bronchiectasis and nodules 19 . Recent studies have shown that the clinical characteristics and prognosis of ABPA are closely related to the mucus plugs in central bronchiectasis 20 .…”
Section: Discussionmentioning
confidence: 97%
“…Studies have reported that high CEA levels in serum and bronchoalveolar lavage uid might connected with mucous embolism in asthma patients 17,18 . Milene Caroline Koch al have also shown that increase CEA levels associated with airway changes in rheumatoid arthritis patients such as bronchial wall thickening, bronchiectasis and nodules 19 . Recent studies have shown that the clinical characteristics and prognosis of ABPA are closely related to the mucus plugs in central bronchiectasis 20 .…”
Section: Discussionmentioning
confidence: 97%
“…The CEA level detected recurrent disease 2 to 5 months prior to discovery by any other means ( 23 , 24 ). Any rise in CEA level higher than 10 ng/mL should prompt thorough assessment for disease recurrence; however, false-positive elevated CEA levels have been reported to occur in patients who are smokers and patients with inflammatory states, including chronic obstructive lung diseases ( 25 ) and rheumatoid arthritis ( 26 ). In addition, the CEA level is not specific to CRC and could be elevated in many other cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In terms of causality, no studies claim to present proof of causality between BE and RA. Sixteen of the included studies self-report as negative studies, 6,14,22,24,26,28,29,30,34,38,39,41,43,44,48,50 while five studies suggested associations based on biological/biochemical processes, 18,21,27,45,51 four based on (temporality of) symptoms 16,25,46,47 and three based on prevalence of radiographic findings. 19,32,36…”
Section: Temporality and Causality Between Rheumatoid Arthritis And B...mentioning
confidence: 99%